The manga artist's handbook : drawing basic characters - Junka Morozumi; Tomomi Mizuna (Tokyo : Tuttle Publishing, 2019)
This book provides a revolutionary new 3-step tracing technique that beginning artists can use to quickly learn to draw manga characters just like a pro!
Keywords: Comic books, strips, etc. Japan Technique; Instructional and educational works Japan